2016
DOI: 10.1080/1064119x.2016.1198944
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the influences of physical parameters on sediment sound speed

Abstract: Based on the core samples collected in different geological tectonic units in the southern South China Sea, the double parameter equations between sediment sound speed and physical parameters were developed. According to the double parameter equations, the influences of physical parameters (porosity, mean grain size, wet bulk density, and clay content) on sediment Downloaded by [University of Lethbridge] at 11:47 22 June 2016 3sound speed were analyzed. In order to analyze the sensitivity of each parameter in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…the system to study the correlation between velocity and physical properties in the Yellow Sea. Hou et al (2015Hou et al ( , 2016 studied the geoacoustic properties of sediments in the southern South China Sea and found that porosity is the most influential factor in physical properties for the sound velocity.…”
Section: Introductionmentioning
confidence: 99%
“…the system to study the correlation between velocity and physical properties in the Yellow Sea. Hou et al (2015Hou et al ( , 2016 studied the geoacoustic properties of sediments in the southern South China Sea and found that porosity is the most influential factor in physical properties for the sound velocity.…”
Section: Introductionmentioning
confidence: 99%